VALIDITAS BOOKLET INVENTARISASI FAMILI MORACEAE SEBAGAI BAHAN PENGAYAAN KONSEP KEANEKARAGAMAN HAYATI DI SMA - Erna Erna; Mahrudin Mahrudin; Riya Irianti (Bioedukasi Jurnal Pendidikan Biologi, 2025)
Twenty-first century education demands that educators possess innovative and creative skills in developing teaching materials that support the achievement of learning objectives. One type of teaching material that can be developed is a booklet. Booklets, as printed learning media, offer several advantages, such as accessibility without an internet connection and the ability to present colorful and visually engaging content. The development of a booklet can incorporate plant diversity materials based on local potential, such as the Moraceae family, which students frequently encounter in their daily lives. The development process includes product feasibility testing, one of which involves assessing its validity. This study aims to describe the validity of the developed booklet. The research employed the Research and Development (R&D) approach using the Plomp model, which consists of five stages. The validity test results showed a score of 91.40%, categorized as “very valid.â€ These findings indicate that the developed booklet is ready to be implemented as enrichment material for the biodiversity concept, as it meets twelve aspects of teaching material validity and has been revised to ensure high quality. The content of the booklet is designed to align with students’ competencies, curriculum requirements, and scientific principles.